Evaluating the Aqueous Phase From Hydrothermal Carbonization of Cow Manure Digestate as Possible Fertilizer Solution for Plant Growth - Celletti, Silvia; Lanz, Maximilian; Bergamo, Alex; Benedetti, Vittoria; Basso, Daniele; Baratieri, Marco; Cesco, Stefano; Mimmo, Tanja (Frontiers in Plant Science, 2021)
Improving the agronomic use of recycled nutrients derived from organic waste is one of the priorities within the measures adopted by the European community to reduce environmental issues, but remains an unexplored area of research. The present study focused on investigating the possibility of using innovative fertilizer solutions in hydroponic systems for the growth of agricultural plants. To this purpose, the liquid fraction (AHL), derived from the hydrothermal carbonization (HTC) of cow manure digestate, was chemically characterized (pH, electrical conductivity, mineral elements, and organic compounds, including phytotoxins), was diluted with distilled water (1:30, 1:60, and 1:90, v/v) to reduce its potential phytotoxicity, and was used to grow hydroponically maize (Zea mays L.) plants, instead of the classical full-strength nutrient solution. The results indicated that the dilution 1:30 of AHL solution maintained a high level of toxicity for the plants (phytotoxic substances, especially Na and alkalinity), inducing the arrest of their growth. Differently, the other two dilutions (i.e., 1:60 and 1:90) seemed to considerably limit the levels of toxicity since they allowed the plants to develop. However, these dilutions were poor in nutrient elements, inducing alteration in photosynthesis and an onset of deficiency symptoms like pronounced leaf chlorosis. In the view of an eco-friendly approach, future studies are therefore needed to identify the correct species-specific dilution ratio, to supply both low levels of phytotoxins and adequate content of essential nutrients for appropriate plant growth and development. Furthermore, in order to lower the specific Na phytotoxicity, treatments are of utmost importance before using AHL as a fertilizer solution.